2019
DOI: 10.1590/s0100-83582019370100043
|View full text |Cite
|
Sign up to set email alerts
|

Residual Activity of Sulfentrazone Applied to Soybean on Cotton Crop in Succession

Abstract: Weed resistance to glyphosate in agricultural production systems has led to the need of applying herbicides with different mechanisms of action. However, the persistence of these herbicides in the soil can harm the subsequent crop. This study aimed to assess the effect of the residual activity of the herbicide sulfentrazone applied in pre-emergence of soybean on cotton in succession. The experimental design was a randomized block design with five replications, with seven doses of sulfentrazone (0, 37.5, 75, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…However, most producers use pre-established herbicide recommendations for management, often without considering the relationship of herbicides with edaphoclimatic factors, with the cultivar used and even with the rotation or succession system implemented in the area. If the herbicides used in the control of cotton stalks persist in the soil, there is the possibility of causing intoxication of the crop sown in succession, this effect being called residual activity or carryover (Mancuso et al, 2011;Oliveira Jr, 2011;Gheno et al, 2015;Gheno et al, 2016;Matte et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, most producers use pre-established herbicide recommendations for management, often without considering the relationship of herbicides with edaphoclimatic factors, with the cultivar used and even with the rotation or succession system implemented in the area. If the herbicides used in the control of cotton stalks persist in the soil, there is the possibility of causing intoxication of the crop sown in succession, this effect being called residual activity or carryover (Mancuso et al, 2011;Oliveira Jr, 2011;Gheno et al, 2015;Gheno et al, 2016;Matte et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The SI for cotton sowing after application of 2,4-D + sulfentrazone treatment, for example, was 87 to 89 days. However, MATTE et al (2019) observed that sulfentrazone had enough residual activity to cause intoxication of sown cotton 112 DAA.…”
Section: Resultsmentioning
confidence: 99%
“…The use of herbicides with residual activity may affect the crop sown in succession. This occurs when the crop is susceptible, the herbicide persists in the soil for longer than the interval between application and sowing of the crop and is available in soil solution in sufficient concentration to be absorbed by plants (GHENO et al, 2016;MATTE et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Por isso, é importante conhecer as propriedades dos solos para a tomada de decisão quanto ao uso de herbicidas como o sulfentrazone, uma vez que, existem processos como a lixiviação e sorção que interferem na ação desse herbicida quando aplicado em préemergência das plantas daninhas (ZANARDO et al, 2019). Além disso, o herbicida é aplicado com frequência em cana-de-açúcar, mas na reforma do canavial (4-5 anos) após a colheita mecanizada, não pode ter mais o herbicida pois pode causar carryover em culturas como sorgo, algodão, cenoura e tomate (DAN et al, 2010;MATTE et al, 2019;RACHUY e FENNIMORE, 2021). Embora o remineralizador não tenha influenciado para potencializar a fitorremediação, a presença do remineralizador contribuiu para o aumento da fertilidade dos solos, principalmente para os teores de P, CTC, Ca e Mg.…”
Section: Análise De Resíduo Biodisponível De Sulfentrazone Com Bioens...unclassified
“…Entre os diversos herbicidas aplicados em pré-emergência com longo período residual nos solos, destaca-se o sulfentrazone{N-[2,4-dichloro-5-[4-(difluorometil)-4,5dihidro-3-metil-5-oxo-1-H-1,2,4-triazol-1-il]fenil]metanosulfonamida} amplamente utilizado no mundo e principalmente no Brasil nas culturas da soja, cana-de-açúcar e eucalipto para o controle plantas daninhas mono e eudicotiledôneas(MATTE et al, 2019, MAPA, 2023. O sulfentrazone apresenta caráter ácido fraco (constante de dissociação ácida, pKa = 6,56), coeficiente de partição octanol-água baixo (Kow = 97,9 em pH 7) e coeficiente de partição normalizado pelo teor de carbono orgânico (Koc = 43 mL g -1 )(SHANER, 2012; PPDB, 2023).…”
unclassified